VD_FINDINFO HC / 2015 / 1091 vom 16. Dezember 2015 - VD Tribunal cantonal (2015)
FRAIS JUDICIAIRES, AUTORISATION DE PROCÉDER | 110 CPC (CH), 207 al. 1 let. c CPC (CH), 319 let. b ch. 1 CPC (CH), 321 al. 1 CPC (CH)